Raising can-do kids : giving children the tools to thrive in a fast-changing world - Rende, Richard; Prosek, Jennifer (Perigee, an imprint of Penguin Random House LLC, 2015)
"In a world that's changing at warp speed, our kids will need to navigate a path to success without a roadmap -- something entrepreneurs do every day. What if we looked to the world of entrepreneurship, in addition to child development experts, for insights on helping kids gain the skills they'll need in order to prosper personally and professionally? Raising Can-Do Kids is the first book to make a link between the essential qualities that make great entrepreneurs tick and what we know about how children learn and grow, offering parents proven ways to raise kids who embrace the uncertain, challenging adventure that is growing up in today's (and tomorrow's) changing world. Each chapter is devoted to a quality -- including curiosity, inventiveness, optimism, opportunity-seeking, compassion, and service -- and reveals how parents can nurture these qualities. Filled with engaging examples and actionable insights, Raising Can-Do Kids introduces a timely new paradigm for parents--one that will help "future-proof" our children and set them up for success on their own terms."--provided from Amazon.com.